Bicyclo-HMX as an Energetic Additive for Composite Propellants - Sazeček, Filip; Vodochodský, Ondřej; Matyáš, Robert; Stojan, Petr; Zigmund, Jan; Pachman, Jiří (American Institute of Aeronautics and Astronautics, 2023)
This paper deals with the ballistic parameters of composite propellants containing bicyclo-HMX (BCHMX) as an energetic additive. The results were compared with the same composite propellant containing HMX. On the basis of the results of the measurement using a Stojan vessel, it was found that the burning rates of BCHMX containing propellants are in most cases higher compared to HMX in propellants. Increasing the concentration of HMX in the propellant often leads to a decrease in burning rate. This trend was not observed for higher concentrations of BCHMX. The pressure exponent of all tested propellants is less than 1, whereby lower values were mostly observed for BCHMX propellant samples. Propellants containing BCHMX are also distinguished by easy ignitability. Using REAL software, it was found that propellants containing BCHMX achieve high specific impulses which, at BCHMX content in the propellant over 30 %, exceed the specific impulse values of the propellant without BCHMX content and all tested propellants containing HMX.
Bicyklo-HMX jako energetické aditivum do heterogeních propelentů
Keywords: Composite Propellants; High Performance Propellants; Adiabatic Flame Temperature; Energetic Materials; Nitramine Propellants; Heterogenní propelenty; vysoce výkonné propelenty; Adiabatická teplota plamene; Energetické materiály; Nitraminové propelenty